CHRISTIAN HUMANISM IN THE THEORY AND PRACTICE OF THE EDUCATIONAL ACTIVITY OF ORTHODOX PRIESTS IN VOLYN (XIX - EARLY XX CENTURIES) - Leliukh S. R. (International Journal of Innovative Technologies in Social Science, 2022)
The article justifies the essence and specificity of Christian humanism as a theoretical phenomenon and the practical basis of the activity of Orthodox priests-educators in Volyn in the 19th and early 20th centuries. It has been found that the Christian humanist foundations of Ukrainian Orthodoxy allows for extrapolating them to the general state of schooling at various historical stages of its development. It has been established that Christian humanism in the educational space of the Volyn region of this period can be considered in both theoretical and practical contexts. The peculiarities of the theory of Christian humanism in the scientific activity of Volyn priests-educators Apollonius Sendulskii, archpriest Andrii Khoynatskii, archbishop Agafangel (Solovyov), archbishop Vitalii (Gregulevych) and others are substantiated. The opinion about the crisis of Christian morality of the 19th century in the daily life of citizens as the object of theoretical investigations of Volyn priests of the studied period is justified. In the context of the practical implementation of the foundations of Christian humanism in the education process in parish schools and spiritual educational institutions in Volyn, the significance of the set of basic Christian virtues that children should learn in the first years of education in parish schools of the Volyn region has been proven. The formulated conclusion is that in the studied period, the Orthodox priesthood of Volyn was based on the theory and practice of Christian humanism from the classical biblical foundations of the training of Christian virtues in children during their education; only occasionally did the priests pay attention to the vast experience of the moral and ethical upbringing of children in the family accumulated by the Ukrainian people, enshrined in national traditions, customs, and rituals.